Stock Valuation Analysis of PT Sinar Mas Agro Resources and Technology Tbk Using Free Cash Flow to The Firm and Relative Valuation - Ramiza, Fitradi; Rahadi, Raden Aswin (Devotion : Journal of Research and Community Service, 2023)
Indonesia is the world's top producer and exporter of palm oil, generating 46 million tonnes of crude palm oil. PT SMART Tbk (SMAR) is one of Indonesia's big palm oil companies, with a plantation area of 136,402 hectares. The Indonesian government implemented the B35 biodiesel policy in February 2023, indicating there is potential for growth in the increased use of palm oil as a biodiesel blend. The positive sentiment from the B35 program, which will continue into the B40 program, is expected to boost domestic market demand for biodiesel, consequently impacting SMAR's sales revenue. The study aims to evaluate SMAR's business performance, intrinsic value, and propose solutions to close the value discrepancy gap. The study adopts a quantitative approach for stock valuation calculations and a qualitative approach for underlying assumptions. The analysis covers financial statement analysis, financial ratio analysis, PESTLE analysis, Porter’s five forces analysis, absolute valuation and relative valuation methods. Based on the FCFF analysis, SMAR's intrinsic value is Rp 8,609 while the market price is Rp 5,200, indicating that SMAR is undervalued. The relative valuation analysis using PER, PBV, and EV/EBITDA also indicates that SMAR is undervalued compared to similar companies in the palm oil industry. Overall, this indicates a potential investment opportunity for investors in SMAR shares.